Soroprevalência de anticorpos contra Leishmania infantum e outras espécies de protozoários e rickettsia em cães - Paulan, Silvana de Cássia [UNESP]; Lins, Aline Gouveia de Souza [UNESP]; Tenório, Michely da Silva [UNESP]; da Silva, Diogo Tiago [UNESP]; Pena, Hilda Fátima de Jesus; Machado, Rosangela Zacarias [UNESP]; Gennari, Solange Maria; Buzetti, Wilma Aparecida Starke [UNESP] (FapUNIFESP (SciELO), 2012)
Canine visceral leishmaniasis (CVL) is caused by the protozoan Leishmania infantum, which infects dogs and humans in many regions of Brazil. The present study involved an indirect fluorescent antibody test (IFAT) to analyze L. infantum, Ehrlichia spp., Babesia canis, Toxoplasma gondii and Neospora caninum infection rates in serum samples from 93 dogs in a rural settlement in Ilha Solteira, SP, Brazil. The seroprevalence rates of anti-L. infantum, anti-Ehrlichia, anti-B. canis, anti-T. gondii and anti-N. caninum antibodies were 37.6%, 75.3%, 72%, 47.3% and 6.4%, respectively. In addition to IFAT, direct microscopic examination of popliteal lymph node aspirates revealed 26.9% of CVL positive dogs. Serological tests revealed that 17.2% of the dogs were seropositive for a single parasite, 29% for two parasites, 33% for three, 16.1% for four, and 1.1% for five parasites, while 3.2% were seronegative for five parasites. The presence of antibodies against these parasites in serum samples from dogs confirmed their exposure to these parasites in this rural area. Because of the potential zoonotic risk of these diseases, mainly leishmaniasis, ehrlichiosis and toxoplasmosis, special attention should focus on programs for the improvement of diagnostic assays and control measures against these parasites.
Seroprevalence rates of antibodies against Leishmania infantum and other protozoan and rickettsial parasites in dogs
Keywords: Babesia; Dogs; Ehrlichia; Leishmania; Neospora; Toxoplasma